Cognitive Radio-Based Power Adjustment For Wi-Fi. - Tat, Chee Wan (2009)
In this paper the idea of using Cognitive Radio (CR) techniques to optimize the access point (AP) configuration for IEEE 802.11 WLAN was exploited. In particular, we address the issue of optimizing AP transmission power and channel allocation within the network.